Effect of doses on the bioavailability of phenytoin from a prompt-release and an extended-release preparation: Single dose study - Noppamas Rojanasthien (2018)
Objective: To determine the effect of doses on the bioavailability of a prompt-release and an extended-release phenytoin capsule after given as single doses. Material and Method: Eight healthy male volunteers were given single oral doses of 100, 200, and 300 mg of a prompt-release preparation (Ditoin□) and an extended-release phenytoin (Dilantin Kapseals□) preparation in a crossover design with a two weeks washout period after an overnight fast. Serial blood samples were collected over 72 h post-dose. Plasma phenytoin concentrations were determined by HPLC and pharmacokinetic parameters were analyzed by non-compartmental model. Results: Rate of phenytoin absorption from the prompt-release preparation was more prolonged after the 300-mg dose (T max 4.5 h) than those of the 100- and 200-mg doses (Tmax 3.5 and 3 h, respectively). Similarly, the Tmax of the 200- and the 300-mg extended-release preparation (5.5 and 4 h) were more prolonged than the 100-mg dose (3 h). Bioequivalence analysis showed that the Cmax of all doses of the prompt-release preparation were higher than those values of the extended-release preparation with the mean Cmax ratio (90% CI) of 1.32 (1.24-1.40), 1.26 (1.14-1.40), and 1.29 (1.10-1.51) for the 100-, 200- and 300-mg doses, respectively. The extent of absorption (AUC0-∞) of 100-mg phenytoin was bioequivalent between the two preparations [mean AUC ratio (90% CI) of 1.15 (1.11-1.18)], however, for higher doses, the prompt-release products produced higher bioavailability than the extended-release products [mean AUC ratio (90% CI) of 1.19 (1.07-1.33) and 1.17 (0.98-1.38), respectively for the 200- and 300-mg doses]. The difference in the bioavailability did not affect the elimination of phenytoin and their half-lives were comparable (11-13 h). Conclusion: The bioavailability of phenytoin from both preparations increased proportionally over the dose range of 100-300 mg, however, the bioavailability of the prompt-release preparation was higher than the corresponding doses of the extended-release product.